An Internet of Things Model for Improving Process Management on University Campus - William Villegas-Ch (Future Internet, 2020)
Currently, there are several emerging technologies that seek to improve quality of life. To achieve this, it is important to establish the various technologies’ fields of action and to determine which technology meets the conditions established by the environment in which it is designed to operate in order to satisfy the needs of society. One type of environment is the university campus. This particular environment is conducive to the development and testing of technological innovations that might later be replicated in larger environments such as smart cities. The technology that has experienced the greatest development and introduction of applications is the Internet of Things. The wide variety of available devices and the wide reach of the Internet have become ideal parameters for the application of the Internet of Things in areas that previously required the work of people. The Internet of Things is seen as an assistant to, or a substitute for, processes that are generally routine and which require the effort of one or more people. This work focuses specifically on processes to improve administrative management in a university through the use of the Internet of Things.